Quercetin Ameliorates Insulin Resistance and Restores Gut Microbiome in Mice on High-Fat Diets - Yuqing Tan; Christina C. Tam; Matt Rolston; Priscila Alves; Ling Chen; Shi Meng; Hui Hong; Sam K. C. Chang; Wallace Yokoyama (MDPI AG, 2021)
Quercetin is a flavonoid that has been shown to have health-promoting capacities due to its potent antioxidant activity. However, the effect of chronic intake of quercetin on the gut microbiome and diabetes-related biomarkers remains unclear. Male C57BL/6J mice were fed HF or HF supplemented with 0.05% quercetin (HFQ) for 6 weeks. Diabetes-related biomarkers in blood were determined in mice fed high-fat (HF) diets supplemented with quercetin. Mice fed the HFQ diet gained less body, liver, and adipose weight, while liver lipid and blood glucose levels were also lowered. Diabetes-related plasma biomarkers insulin, leptin, resistin, and glucagon were significantly reduced by quercetin supplementation. In feces, quercetin supplementation significantly increased the relative abundance of Akkermansia and decreased the Firmicutes/Bacteroidetes ratio. The expression of genes Srebf1, Ppara, Cyp51, Scd1, and Fasn was downregulated by quercetin supplementation. These results indicated that diabetes biomarkers are associated with early metabolic changes accompanying obesity, and quercetin may ameliorate insulin resistance.